Understanding counterplay in video games - Meades, Alan F. (Routledge advances in game studies, 2015)
This book offers insight into one of the most problematic and universal issues within multiplayer videogames: antisocial and oppositional play forms such as cheating, player harassment, the use of exploits, illicit game modifications, and system hacking, known collectively as counterplay